NUMERICAL INVESTIGATION OF A DIVERGENT EXHAUST DIFFUSER OF A GAS TURBINE ENGINE - PRASHANT CHANNAVEERE,; DR.YOGANANDA A (International Journal of Innovations in Engineering Research and Technology, 2021)
This papermainlydeals with the numerical analysis of 3Dmodel of adivergent exhaust diffuserof a gas turbine engine, which is developed to study theco-efficient of pressure recovery, exit velocity, static pressure and dynamic pressure. The variation in divergent exit diameters of an exhaust diffuser are 242.25mm, 247.25mm, 252.25mm and the inlet diameter value as 140mm and the methodology affects the flow through an exhaust diffuser. Results of CFD analysiswill givethe optimum value of co-efficient of pressure recoveryof a divergent exhaust diffuser.The maximum value of co-efficient of pressure recovery will leads to improve the performance and efficiency of a turbine.It also verifiedthat the CFD is a convenient tool for designing and analysingthe flow through a divergent exhaust diffuser.